2015
DOI: 10.1007/s12011-015-0355-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Arsenic Levels in Smokeless Tobacco Products and Biological Samples of Oral Cancer Patients and Control Consumers

Abstract: It has been extensively reported that chewing of smokeless tobacco (SLT) can lead to cancers of oral cavity. In present study, the relationship between arsenic (As) exposure via chewing/inhaling different SLT products in oral cancer patients have or/not consumed SLT products was studied. The As in different types of SLT products (gutkha, mainpuri, and snuff) and biological (scalp hair and blood) samples of different types of oral cancer patients and controls were analyzed. Both controls and oral cancer patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
1
9
0
1
Order By: Relevance
“…Another study in Taiwan has concluded that besides cigarette smoking and betel quid chewing, arsenic in farm soils may be an important factor for the development of oral carcinoma in this population (Su et al 2010). This is consistent with another study in Pakistan where positive association has been found out between the arsenic poisoning and the occurrence of oral carcinoma (Arain et al 2015). In India, studies have been carried out proving a positive association between the arsenic toxicity and OSCC , Pal et al 2018.…”
Section: Association Of Arsenic and Cancers (International Scenario)supporting
confidence: 78%
See 1 more Smart Citation
“…Another study in Taiwan has concluded that besides cigarette smoking and betel quid chewing, arsenic in farm soils may be an important factor for the development of oral carcinoma in this population (Su et al 2010). This is consistent with another study in Pakistan where positive association has been found out between the arsenic poisoning and the occurrence of oral carcinoma (Arain et al 2015). In India, studies have been carried out proving a positive association between the arsenic toxicity and OSCC , Pal et al 2018.…”
Section: Association Of Arsenic and Cancers (International Scenario)supporting
confidence: 78%
“…This may account for continuous lifelong immune suppression and chronic oral graft-versushost disease (Elad et al 2010). Recently, metal toxicity through drinking water intake has also emerged as a potent risk factor (Su et al 2010, Arain et al 2015, Pal et al 2018. The relation between these risk factors and the occurrence of this malignancy is well stated in developing countries like India, related to the arrangement of different summits and meets, especially in North Eastern India, the recent one in Agartala, Tripura.…”
Section: Causesmentioning
confidence: 99%
“…Smokeless tobacco may also contain harmful metals such as arsenic. A recent study indicates that the concentration of arsenic was significantly higher in scalp hair and blood samples of tobacco chewing patients than those of controls 4 .…”
Section: Introductionmentioning
confidence: 90%
“…However, its effect in oral carcinoma is not well studied. A few studies in Taiwan, Pakistan and India have indicated its positive correlation with the occurrence of this carcinoma (Su et al, 2010, Arain et al, 2015, Pal et al, 2017, 2018. Since West Bengal is the most affected state in India, we have chosen this metal toxicity as a possible cofactor or an independent risk factor in the oral carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…These two areas are the worst affected areas in the world (Ratnaike, 2003). It has also been reported that arsenic toxicity may lead to the occurrence of oral carcinoma in various places (Su et al, 2010, Arain et al, 2015, Pal et al, 2017, 2018 apart from skin, lung and bladder carcinoma. So, our aim of this study is to find out whether the effect of addictions or the metal toxicity through drinking water intake is acting as the most potent factor in the development of oral carcinoma and correlate these three; selecting the population of West Bengal, India.…”
Section: Introductionmentioning
confidence: 99%